Une église au sommet du château de Penne (Tarn) - Florence Guillot; Jean Catalo; Charles Peytavie; Nicolas Portet; Adeline Béa; Philippe Pergent (Archéologie Médiévale)
The castle of Penne (Tarn—Occitanie) is a fortification on a summit mentioned from the beginning of the 11th century. The restoration is underway since 2006. A collective research program and archaeological excavation have recently re-examined this site. They allowed the castle to be placed in the context of its seigneury and to rediscover the area of an earlier castrum occupied before the mid-thirteenth century, much larger than the fortified Capetian-style built in the last quarter of the 13th century and the beginning of the 14th century. Excavations took place on the highest platform of the summit. A castle chapel made up of successive buildings has been studied. The first sanctuary was established around the year 1000. It was modified in the second half of the 12th century, when its apse was transformed into a flat chevet built on a vault above the void. But it was mainly in the first decades of the 13th century that the church changed shape, with the construction of an elaborate Gothic nave preceded by a perron entrance overlooking a forecourt. When the entire fortification was reworked by the French royal authority into a Capetian-style castle—during the last quarter of the 13th century and the beginning of the 14th—the church was framed between high towers and lost its pre-eminence at the prow of the summit. It was endowed with exceptional stained-glass, but these were removed at the end of the 14th century to recover lead. The chapel was then more or less repaired and maintained until its destruction during the French Revolution.